The Influence Of Social Media and Business Communication On The Development Of The Warkop Seulawah Kupi Business In Medan City - Putri Najwa Safitri; Laras Fitri Aini Hasibuan; Irene Checilia Sihotang; Hera Wati; Wisnu Rayhan Adhitya (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The study aims to analyze the influence of business communication and social media on the growth of Warkop Seulawah Kupi in Medan City. The number of customers and popularity of Warkop Seulawah has increased in recent years. It is suspected that the main factor in this development is the effective use of social media and good business communication with suppliers, distributors and other business partners. The method used is quantitative using multiple linear regression analysis techniques . The research results show that the two independent variables of business communication and social media have a positive and significant influence on the business development of Warkop Seulawah. The results provide traditional businesses with an understanding of how important it is to utilize social media and business communications to face competition in the digital era.